Formulation and evaluation of rice bran oil nanoemulsion for cosmetic application by using sucrose monoester / Siti Syahirah Md Radzi - Md Radzi, Siti Syahirah (2007)
Nanoemulsions are a class of emulsions with fine droplet size in the range of 20-500nm. Nanoemulsions are not thermodynamically stable and because of that their characteristics will depend on the preparation method. The aim of this study is to investigate the effect of formulation and preparation variables of nanophase gel as pre-nanoemulsion over nanoemulsion properties. Pre nanoemulsion formulation was first developed by varying sucrose monoester, glycerol/water (8:2) and safflower oil composition to form cubical liquid crystalline system or nanophase gel. Then an emulsion in nano droplet size was produced by the mixing of pre-nanoemulsion with distilled water under gentle and agitation. The effects of different mechanical energy on droplet size and stability of nanoemulsion were then determined with respect to the variation of sucrose monoester and safflower oil composition. Pre-nanoemulsion formulation uses sucrose monoester combination produces smaller droplet size. However, pre-nanoemulsion formulation uses single sucrose monoester unable to produce nanoemulsion as it may separate after promote to the water. In this study, there was no significant different in particles size in terms of using different mechanical energy which were homogenizer and stirrer. The main mechanism of this nanoemulsion breakdown by using high energy emulsification method might be due to coalescence phenomenon. In addition, destabilization of nanoemulsion in long term process could be attributed to Ostwald ripening.